Facile transformation of graphene oxide nanospheres based on AAO template - Riad M. Hameed; Ahmed Al-Haddad; Abbas K.H. Albarazanchi (Kuwait Journal of Science)
In this paper, a facile one-step drop method is developed to convert reduced graphene oxide into graphene oxide nanoparticles. An aqueous solution of reduced graphene oxide is poured through the pores of anodic aluminum oxide templates to form graphene oxide nanospheres at low temperature (120 ​°C) and low pressure (0.8 ​bar) preparation conditions. Electrochemical exfoliation of graphite and reduced graphene oxide nanospheres (not hollow) were adopted to fabricate reduced graphene oxide within the pores of an anodic aluminum oxide template. The prepared reduced graphene oxide nanospheres show uniform diameters (∼42.5 ​nm) and a low O/C ratio (8%). Graphene nanospheres achieve higher sensitivity to CO2 gas in air (at room temperature) compared to graphene oxide nanosheets (i.e., in contrast to carbon dioxide gas sensors in graphene sheets). Its sensitivity increased to 35% by shaping the nanosheets to nanospheres of reduced graphene oxide which is attributed to a surface area expansion of 7.4 ​× ​105 times. Moreover, graphene oxide, reduced graphene oxide, and reduced graphene oxide nanospheres show a fast response time of 0.19 ​s, 0.24 ​s, and 0.31 ​s, and short recovery times of 1.14 ​s, 1.17 ​s, and 1.22 ​s, respectively, with higher sensitivity of reduced graphene oxide nanospheres.